A bibliographical survey of Iloko linguistics, 1621-1974 with a preliminary bibliography of Iloko linguistics - Foronda, Jr., Marcelino A. (1976)
This bibliographical survey focuses attention on the development of Iloko linguistics by including a listing of materials written and/or published in Spanish, English, French, German, and, of course, Iloko from 1621, when the first book in Iloko was published, to 1974, when interest in things Philippine (and this includes Iloko linguistics) was on the rise due to what has been termed as a Philippine cultural renaissance.
Includes bibliographical references.